Aqad Syirkah: Dalam Kompilasi Hukum Ekonomi Syariah Dan Mazhab Maliki - Sudarto, Aye; Mustofa, Muhamad Bisri; Mu’in, Fathul (Universitas Islam Negeri Raden Intan Lampung, 2022)
Law No. 3 of 2006 concerning Religious Courts (PA) provides significant changes regarding the position and existence of PA in Indonesia. The PA's authority is 1) family law cases, 2) sharia economic cases. Follow up on the authority in the field of Islamic economics. KHES was ratified through Supreme Court Regulation (Perma) No. 2 of 2008 concerning the Compilation of Sharia Economic Law. One of the themes in KHES and which is quite widely used by the community is the Syirkah Agreement. The provisions on Syirkah in KHES are contained in Book II Chapter VI concerning Syirkah and Ownership Syirkah. KHES allows all forms of syirkah contracts which include syirkah inan, syirkah abdan, syirkah mufawadhah, syirkah wujuh and syirkah mudharabah. The Maliki School allows shirkah inan, shirkah abdan, and shirkah mufawadhah but does not allow syirkah wujuh. Syirkah is valid because it is only related to the value of property and work. Meanwhile, there are no two main elements in syirkah wujuh. The Maliki school also does not include syirkah mudarabbah as a form of syirkah. Because the Maliki School supports Mudharabah as a separate contract, in other forms of cooperation. Keywords: KHES, Sharia Economic Law, Maliki School, Syirkah